Intervensi Politik dan Militer Rusia Terhadap Ukraina Sebagai Wujud Penerapan Strategi Deterens - Moh. Talabul Amal; Ali Muhammad; Takdir Ali Mukti (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
This study aims to determine the background of Russia's intervention in Ukraine through the approach of the concept of deterrence. To reveal this, this study uses a qualitative-explanatory method aimed at presenting a depth of analysis with the context of testing the hypothesis and the relevance of two variables. The results of the study reveal that the background of Russia's intervention in Ukraine is to respond to threats from the expansion of NATO's membership wing in Eastern Europe, especially Ukraine. In addition, Russia is also driven by the existence of Russian national interests in the territory of Ukraine and the Crimean Peninsula to secure its influence in Ukraine and reject the influence of the United States in Eastern Europe. Russia's intervention in Ukraine is seen as an effort to prevent Ukraine from joining the European Union. Russia is considered not to respect Ukraine's sovereignty over the act of annexing the Crimean peninsula in 2014 and the military invasion of Ukraine in 2022. The limitation of this research is that the data used is still limited to the type of secondary data, namely journals containing data on Russia's intervention against Ukraine.